Urban Acupuncture as a Strategy to Enhance Social Interaction and Renewal in the Context of Urban Renewal Policies (Journal of Planner and Development, 2024)
Abstract: Cities around the world are a major source of urban challenges, facing multiple problems ranging from environmental pollution and depletion of natural resources to urban degradation and lack of social interaction. This research aims to explore the role of urban acupuncture as an innovative strategy in the context of urban renewal policies. The study addresses the two concepts separately, where urban tingling is understood as small, specific interventions aimed at stimulating activity and social interaction in specific areas of the city, while urban renewal deals with comprehensive improvements that include various aspects of the city. The thesis aims to analyze the role of urban acupuncture in the context of urban renewal policies, and to understand how to employ this strategy to enhance social interaction and renewal in cities. It enhances the activity and sustainability of specific areas in the city.